Reproductive and Productive Performance of Crossbred and Terai Cattle in Bardiya District of Nepal - Gautam, Gokarna; Khadka, Ujjwal (Journal of Nepal Agricultural Research Council, 2022)
To compare the reproductive and productive performance of exotic crossbreds and indigenous Terai cattle under farmers' management condition, a household survey was carried out in 218 households of Bardiya, Nepal. Total of 262 cows [Jersey cross (n=107), Holstein cross (n=24) and indigenous Terai cattle (n=131)] were considered to determine the production and reproduction parameters. The age at first calving in months was the lowest in Jersey crossbred (27.8±1.8) followed by Holstein cross (29.5±4.0) and Terai cattle (45.7±3) (P<0.05). However, the number of services per conception, calving to conception interval (in months) and inter-calving interval (in months) were shorter in Terai cattle (1.3±0.7, 3.4±1.4 and 12.6±1.9) compared to Jersey cross (1.7±1.3, 4.4±2.2 and 13.5±3.1) and Holstein cross (1.8±0.9, 5.7±2.8 and 14.9±4.7), respectively (P<0.05). Total 6.5% of cattle had a history of reproductive problems; Incidence of repeat breeding tended (P<0.1)) to be higher in Jersey cross (8.4%) and Holstein cross (8.3%) than in Terai cattle (3.0%). Daily peak milk yield (L/day) was significantly lower in Terai cattle (1.7±1.1) than Jersey cross (13.5±3.1) and Holstein cross (14.9±4.7). The lactation length (months) was significantly shorter in Terai cattle than exotic crossbreds. Consequently, the length of dry period (in months) was significantly longer in Terai cattle (5.2±2.1) than in Jersey cross (2.5±0.9) and Holstein cross (2.2±0.7). The reproductive performance parameters in exotic crossbred cows under the farmers' management condition were satisfactory; however, their productivity was low. Thus, the good reproductive traits and variations in productivity of Terai cattle can be utilized in cross breeding programs.